Odpowiedzi

Najlepsza Odpowiedź!
2010-03-19T15:00:52+01:00
Rozwiąż równania:
a) ⅖ (3 - x) = -2 /*5/2
3 - x=-5
x=3+5
x=8
b)¾ (2 - 3x) = -6 /*4/3
2 - 3x=-8
3x=10
x=10/3=3 i 1/3
c)¹/₅ ( x-3) = 9-x /*5
x-3=45-5x
x+5x=45+3
6x=48
x=8
d)0,6 +x
________ = x+1 /*2
2

0,6+x=2x+2
x=0,6-2
x=-1,4
2010-03-19T15:04:25+01:00
A) ⅖ (3 - x) = -2
6/5-2/5x=-2
3i1/5=2/5x//:2/5
x=8
b)¾ (2 - 3x) = -6
3/2-9/4x=-6
7i1/2=9/4x//:9/4
x=3i1/3
c)¹/₅ ( x-3) = 9-x
1/5x-3/5=9-x
6/5x=48/5//:6/5
x=8

d)0,6 +x
________ = x+1//*2
2

0,6+x=2x+2
x=-1,4